Grammatical Interference On English Caption On Facebook Group’s “We Are ASEAN” - Mukshin Berry Chandra; Susilo Susilo; Desy Rusmawaty (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2021)
Abstract In this era, social media become a new way to connect the people. Platform such as, Facebook, Instagram, Twitter are examples of social media that use by large people. People not only share their photos or videos but they also can share their opinions and their knowledge to others as the way to build communication as social beings. On social media, there is a tool to make a group. Usually people make a group on social media based on their background, hobbies and discussion about certain issues. On Facebook group there is a group consisting of people from South East Asia named "We Are ASEAN”. On this group they discuss their opinions, stories and sometimes they introduce their culture to each other. Because of the variety of culture the language that is used in that group is English language. In this research was aimed to find the types and the most common mistake grammatical error in synthetic level on the group. The design of this research was content analysis by using qualitative approach and the researcher was the key instrument. The researcher took the samples by screen shooting twenty posters published by Indonesian people on Facebook group from July to September 2021. The researcher used document analysis to analyze the document as the samples and find out the grammatical error based on the syntactic level. The researcher found 69 mistakes was considered as grammatical interferences on English caption. This research found 10 types of grammatical errors in the samples. Types of grammatical errors were found by researcher such as; tenses, plurality, subject-verb, preposition, pronoun, noun phrase, article, diction, capital letter, auxiliary, and translation. Most of grammatical errors were found by researcher thet happened in capital letters case. The researcher found 34 errors in capital letters case with 47% in total grammatical errors. The researcher also explain the grammatical errors in syntactic level based on the error itself. From those results, capital letters became the common mistake found in second language accusations process. Capital letters errors on syntactic level can cause confusion in conveying information. Therefore, it is suggested that the writers should recognize the differences rules in target language accusations. The writers should be more aware in second language rules by considering the interference theory in syntactic level based on linguistics knowledge.